PCDH19‐related epileptic encephalopathy in a male mosaic for a truncating variant. Issue 6 (26th March 2016) - Thiffault, Isabelle; Farrow, Emily; Smith, Laurie; Lowry, Jennifer; Zellmer, Lee; Black, Benjamin; Abdelmoity, Ahmed; Miller, Neil; Soden, Sarah; Saunders, Carol
Abstract : Variants in the X‐linked gene PCDH19 are associated with early infantile epileptic encephalopathy‐9. This unusual condition spares hemizygous males except for psychiatric and behavioral abnormalities, and for this reason is also known as female limited epilepsy. Some cases are due to de novo PCDH19 variants, but may also be paternally inherited. Our patient is a 6‐year‐old male with epileptic encephalopathy. Exome sequencing revealed apparent heterozygosity in PCDH19 for a novel nonsense variant, c.605C>A (p.Ser202*), inconsistent with expectations for a male. Testing of other tissues revealed a mixture of mutant and normal alleles. These results are consistent with somatic mosaicism for p.Ser202*. This is the second male with somatic mosaicism for PCDH19 deficiency, providing further support for cellular interference as the pathogenic mechanism for this condition, which leads to this unusual mode of inheritance in which females are more severely affected than males. © 2016 Wiley Periodicals, Inc.